Beta-Hydroxybutyrate, Friend or Foe for Stressed Hearts - Chu, Yuxin; Zhang, Cheng; Xie, Min (Frontiers in Aging, 2021)
One of the characteristics of the failing human heart is a significant alteration in its energy metabolism. Recently, a ketone body, β-hydroxybutyrate (β-OHB) has been implicated in the failing heart’s energy metabolism as an alternative “fuel source.” Utilization of β-OHB in the failing heart increases, and this serves as a “fuel switch” that has been demonstrated to become an adaptive response to stress during the heart failure progression in both diabetic and non-diabetic patients. In addition to serving as an alternative “fuel,” β-OHB represents a signaling molecule that acts as an endogenous histone deacetylase (HDAC) inhibitor. It can increase histone acetylation or lysine acetylation of other signaling molecules. β-OHB has been shown to decrease the production of reactive oxygen species and activate autophagy. Moreover, β-OHB works as an NLR family pyrin domain-containing protein 3 (Nlrp3) inflammasome inhibitor and reduces Nlrp3-mediated inflammatory responses. It has also been reported that β-OHB plays a role in transcriptional or post-translational regulations of various genes’ expression. Increasing β-OHB levels prior to ischemia/reperfusion injury results in a reduced infarct size in rodents, likely due to the signaling function of β-OHB in addition to its role in providing energy. Sodium-glucose co-transporter-2 (SGLT2) inhibitors have been shown to exert strong beneficial effects on the cardiovascular system. They are also capable of increasing the production of β-OHB, which may partially explain their clinical efficacy. Despite all of the beneficial effects of β-OHB, some studies have shown detrimental effects of long-term exposure to β-OHB. Furthermore, not all means of increasing β-OHB levels in the heart are equally effective in treating heart failure. The best timing and therapeutic strategies for the delivery of β-OHB to treat heart disease are unknown and yet to be determined. In this review, we focus on the crucial role of ketone bodies, particularly β-OHB, as both an energy source and a signaling molecule in the stressed heart and the overall therapeutic potential of this compound for cardiovascular diseases.